2010
DOI: 10.1182/blood-2009-04-214668
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation for subtype classification and prediction of treatment outcome in patients with childhood acute lymphoblastic leukemia

Abstract: Despite improvements in the prognosis of childhood acute lymphoblastic leukemia (ALL), subgroups of patients would benefit from alternative treatment approaches. Our aim was to identify genes with DNA methylation profiles that could identify such groups. We determined the methylation levels of 1320 CpG sites in regulatory regions of 416 genes in cells from 401 children diagnosed with ALL. Hierarchical clustering of 300 CpG sites distinguished between T-lineage ALL and B-cell precursor (BCP) ALL and between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
116
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 49 publications
(64 reference statements)
19
116
1
1
Order By: Relevance
“…Nevertheless, methylation analysis of multiple genes in leukemia is yet to be explored as a method for grouping patients (Milani et al, 2010).…”
Section: Dna Hypermethylation Of Cell Cycle and Apoptotic Genes In Pementioning
confidence: 99%
“…Nevertheless, methylation analysis of multiple genes in leukemia is yet to be explored as a method for grouping patients (Milani et al, 2010).…”
Section: Dna Hypermethylation Of Cell Cycle and Apoptotic Genes In Pementioning
confidence: 99%
“…This statement was supported by 4 PCSs [193][194][195][196] that met the inclusion criteria for our SR. Two of the studies 193,194 were deemed to have a low risk of bias, and the other 2 195,196 were deemed to have a low to moderate risk of bias. None of these studies were found to have methodological flaws that would raise concerns about the studies' findings.…”
mentioning
confidence: 70%
“…Nevertheless, only a few studies in the SR specifically mention or allude to the use of preserved cells as the specimen source for the studies performed. [193][194][195][196] Historically, cryopreservation was the most commonly employed method of preserving cells. 197 Cryopreserved leukemia cells can be used for the extraction of DNA and RNA for molecular genetic studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data reported by Yang et al (2009) demonstrated that detection of epigenetic alterations allows the identification of ALL patients with poor prognosis within the standard-risk group. More recently, Milani L et al (2010), analyzing the methylation patterns of CpG sites in 416 genes, have found a striking difference in the methylation patterns within a large number of samples from ALL patients. Notably, they observed a correlation between the methylation level and clinical outcome within major subgroups of ALL patients, identifying 20 genes with DNA methylation levels capable to predict leukemia relapse.…”
Section: Dna Methylationmentioning
confidence: 99%